2008
DOI: 10.1080/01612840802048865
|View full text |Cite
|
Sign up to set email alerts
|

Nobody Was Out Back Then: A Grounded Theory Study of Midlife and Older Lesbians with Alcohol Problems

Abstract: This explorative study used grounded theory methodology (GTM) to develop a substantive theory regarding the life experience of the misuse of alcohol among midlife and older lesbians. The core category in this study is represented by the overarching process of "Disconnecting from their Authentic Selves." Professional health care providers may better be able to understand and assist midlife and older lesbians who misuse alcohol by being aware of their life experience with alcohol problems and the concepts they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Researchers have sought to illuminate factors such as internal identity conflicts (Pettinato 2008; Wong et al. 2008), the centrality of gay bars as safe havens and networking resources (Caceres and Cortinas 1996; Kerby et al.…”
Section: Alcohol Gender and Sexualitiesmentioning
confidence: 99%
“…Researchers have sought to illuminate factors such as internal identity conflicts (Pettinato 2008; Wong et al. 2008), the centrality of gay bars as safe havens and networking resources (Caceres and Cortinas 1996; Kerby et al.…”
Section: Alcohol Gender and Sexualitiesmentioning
confidence: 99%
“…In this study, the majority of women (66%) reported experiencing adverse consequences of alcohol use and 62% of the women had at least one symptom of alcohol dependence. In a qualitative study of 13 midlife and older lesbian women in recovery from alcohol dependence, Pettinato (2008) found that women reported that they used alcohol to “disconnect” from the discomfort associated with “coming out” as a lesbian. In rural African American women, Boyd, Baliko, Cox, and Tavakoli (2007) found that those with alcohol dependence had fewer uplifting events, higher levels of emotion-focused coping, and more positive beliefs about the effects of alcohol than those without alcohol dependence.…”
Section: Resultsmentioning
confidence: 99%
“…(continued) (born before 1952), "Liberation" (born between 1952 and 1967), "Gay Rights" (born after 1967); found that women who came out at a younger age were more likely to experience negative consequences of drinking (e.g., lifetime dependency); results indicated that identity development may be partial explanation for higher rates of drinking-related problems reported by lesbians. Pettinato (2008) Health/health care Grounded theory; constant comparative analysis of in-depth interviews with sample of midlife and older lesbians (n = 13); coding Identified major themes, subthemes: disconnection from the self related to lesbian identity; misuse of alcohol; family issues (e.g., marriage, childbearing); identified need for health care providers to become more aware of unique needs of this population. Phillips and Marks (2008) Health/health care; discrimination Discourse analysis of content of marketing brochures (n = 9); purposive sampling, focus group (n = 6) The dominant discourse marginalized older lesbians through the exclusion of nonheterosexual relationships in both graphics and written text.…”
Section: Methodsmentioning
confidence: 99%